ICAA13: 13th International Conference on Aluminum Alloys 2012
DOI: 10.1002/9781118495292.ch212
|View full text |Cite
|
Sign up to set email alerts
|

Role of Solute and Transition Metals in Grain Refinement of Aluminum Alloys under Ultrasonic Melt Treatment

Abstract: It is well known that several factors affect the as-cast microstructure through influencing either nucleation or growth during solidification. The effect of solute elements on grain refinement, which can be quantified by the growth restriction parameter Q, is of great importance for controlling the as-cast grain size in aluminum alloy. On the other hand, the ultrasonic melt treatment (UST) is one of potent grain refining methods in aluminum alloy. Our previous results showed that ultrasonic melt treatment resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Compared with the alloy without UTs, the tensile yield strength, the ultimate tensile strength, and elongation at break were all significantly increased. Similar research was reported in and Zhang et al (2012), among others. In comparison, the effects of UTs on Sn-based lead-free solder alloy have seldom been investigated.…”
Section: Introductionsupporting
confidence: 90%
“…Compared with the alloy without UTs, the tensile yield strength, the ultimate tensile strength, and elongation at break were all significantly increased. Similar research was reported in and Zhang et al (2012), among others. In comparison, the effects of UTs on Sn-based lead-free solder alloy have seldom been investigated.…”
Section: Introductionsupporting
confidence: 90%